SUBCLINICAL MAGNETIC RESONANCE IMAGING MARKERS OF CEREBRAL SMALL VESSEL DISEASE IN RELATION TO AMBULATORY BLOOD PRESSURE MEASUREMENTS. (June 2022) - Melgarejo, Jesus; Maestre, Gladys E.; Gutierrez, Jose; Thijs, Lutgarde; Mena, Luis; Gaona, Ciro; Reinier, Leendertz; Lee, Joseph; Chavez, Carlos; Calmon, Gustavo; Silva, Egle; Wei, Dongmei; et al.
Abstract : Objective: 24-h and nighttime blood pressure (BP) levels are the strongest BP measurements associated with cardiovascular risk. However, it remains undocumented which of the ambulatory BP measurements have the strongest association and predictive information in relation to the presence of cerebral small vessel diseases (CSVD). Design and method: A subset of Maracaibo Aging Study with 429 participants [aged 40 years or older (women, 73.7%; mean age, 59.3y)] underwent baseline brain magnetic resonance imaging to visualize CSVD, which included log-transformed white matter hyperintensities (log-WMH), the presence (yes/no) of silent brain infarcts (SBI), cerebral microbleeds (CMB), or enlarged perivascular spaces (EPVS). Linear and logistic regression models were applied to examine the association between CSVD and each + 10 mmHg increment in the office and ambulatory systolic BP. Improvement in the fit of nested logistic models was assessed by the log-likelihood ratio and the generalized R2 statistic. Results: Office and ambulatory systolic BP measurements were related to log-WMH (beta correlation coefficients above 0.08; P < 0.001). SBI and CMB were only associated with ambulatory systolic BP measurements (odds ratios [OR] ranged from 1.31 [95% confidence interval, 1.10 1.55] to 1.46 [1.17–1.84], P < 0.003). Accounted for daytime systolic BP, both the 24-h (beta correlation, 0.170) and nighttime (beta, 0.038) systolic BP measurements remained related to log-WMH. When accounted for 24-h or daytime systolic BP levels, the nighttime systolic BP retained the significant association with SBI (ORs, 1.05–1.06; 95% CIs, > = 1.01to< = 1.13), whereas the 24-h and daytime systolic BP levels were not associated with SBI after adjustments for nighttime systolic BP (ORs, < = 0.88; 95% CI, > = 0.77to< = 1.14). On top of covariables and office systolic BP, ambulatory systolic BP measurements significantly improved model performance (R2<3.82%). Compared to 24-h and daytime SBP, nighttime systolic BP had the strongest improvement in the model performance; for WMH (1.46% vs. 1.05%) and SBI (3.06% vs. below 2.05%). Conclusions: 24-h and nighttime systolic BP were the more robust BP measurements associated with CSVD, but for log-WMH and SBI, the nighttime systolic BP level had the strongest association. Controlling ambulatory BP levels might provide additional improvement in the prevention of CSVD